Low power design implementation of a signal acquisition module - Thakur, Ravi Bhushan (Kansas State University, 2010)
As semiconductor technologies advance, the smallest feature sizes that can be fabricated get smaller. This has led to the development of high density FPGAs capable of supporting high clock speeds, which allows for the implementation of larger more complex designs on a single chip. Over the past decade the technology market has shifted toward mobile devices with low power consumption at or near the top of design considerations. By reducing power consumption in FPGAs we can achieve greater reliability, lower cooling cost, simpler power supply and delivery, and longer battery life. In this thesis, FPGA technology is discussed for the design and commercial implementation of low power systems as compared to ASICs or microprocessors, and a few techniques are suggested for lowering power consumption in FPGA designs. The objective of this research is to implement some of these approaches and attempt to design a low power signal acquisition module. Designing for low power consumption without compromising performance requires a power-efficient FPGA architecture and good design practices to leverage the architectural features. With various power conservation techniques suggested for every stage of the FPGA design flow, the following approach was used in the design process implementation: the switching activity is addressed in the design entry, and synthesis level and software tools are utilized to get an initial estimate of and optimize the design’s power consumption. Finally, the device choice is made based on its features that will enhance the optimization achieved in the previous stages; it is configured and real time board level power measurements are made to verify the implementation’s efficacy
Keywords: Low power design; FPGA; Verilog; Cyclone II; Engineering, Electronics and Electrical (0544)